SYNTHESIS, STRUCTURAL CHARACTERIZATION, AND MAGNETIC PROPERTIES OF THE PEROVSKITE COMPOUND EU_{1-X}SR_{X}FEO_{3} - Mohammad Rahman, Raihan
The perovskite oxide compound Eu1-xSrxFeO3 was studied to determine the effect of Sr doping on changes in its structure and magnetic properties. Synthesis of Eu1- xSrxFeO3 for x=0, 0.1, 0.2, 0.3, and 0.4 was carried out using the sol-gel method and structural characterization was analyzed based on the XRD patterns. The single phase of the Eu1-xSrxFeO3 compound is obtained up to x=0.3. Single phase EuFeO3 refinement can be used for XRD patterns with low Sr doping (x?0.1). This indicates the crystal structure has not changed at low Sr doping. However, at high Sr fractions (x?0.2), there is a phase segregation at the crystal structure which is characterized by the appearance of the new peaks in the XRD pattern. Therefore, refinement using single phase EuFeO3 is not suitable and two phases refinement of EuFeO3 and Eu1/3Sr2/3FeO3 is needed. Refinement results and tolerance factor values show that phase segregation occurs in the perovskite material. The results of the refinement also show that the unit cell volume and average bond length of Fe-O decrease with increasing Sr content. These results indicate the formation of Fe4+ ions due to Sr doping. For x=0.1, an anomaly of the unit cell volume is found. Furthermore, the results of magnetization measurements on the Eu1-xSrxFeO3 compound show the presence of weak ferromagnetism and antiferromagnetism components based on its magnetic hysteresis curve. Modification of Jiles-Atherton modeling on the hysteresis curve shows that saturation magnetization and antiferromagnetic interactions increase with increasing Sr fraction. The ferromagnetic component of the perovskite increases due to the formation of Fe4+, while the antiferromagnetic interactions increase due to the increase in the Fe-O2- Fe bond angle. The existence of these two magnetic components indicates that the Eu1-xSrxFeO3 compound has a canted antiferromagnetic system